Phytochemistry and Pharmacology of Indian Traditional Plant Hyssop (Hyssopus officinalis L.): A Review - Kumar, Vanktesh; Kaur, Navjot; Kaur, Arvinder; Wadhwa, Pankaj (Natural Products Journal, The, 2023)
Hyssopus officinalis is a traditional medicinal plant that belongs to the family Lamiaceae, which has been used for centuries for various purposes like carminative, expectorant, and cough reliever. It has been used for the treatment of numerous diseases in patients such as ulcers, asthma, jaundice, leprosy, dropsy, bronchitis, COPD, diabetes, AIDS, bacterial and fungal infections as an herbal remedy due to its fewer side effects and is more efficacies than other traditional medicine. Major classes of chemical compounds found in H. officinalis essential oil are bicyclic monoterpenes, monoterpenoids, acyclic monoterpenes, phenolic monoterpenoids, monocyclic monoterpenes, monocyclic sesquiterpenes, tricyclic sesquiterpenes, bicyclic sesquiterpenes, tricyclic sesquiterpenoids, straight chain saturated hydrocarbons. Some of the major chemical constituents present in the H. officinalis are β-pinene, α-pinene, 1, 8-cineole, apigenin, diosmin, caffeic acid, rosmarinic acid, cis-pinocamphone, trans-pinocamphone, iso-pinocamphone, pinocarvone, which are responsible for its various pharmacological activity. Various studies have been performed on the pharmacological activity of its extract, such as antioxidant, antimicrobial, anti-diabetic, anticancer, antiviral, antiinflammatory, analgesic, anti-leishmanial, anthelmintic, anti-protozoal, and anti-anxiety. Recently, it is used as an anticancer agent and has been demonstrated by studying its cytotoxic and apoptotic effects on breast cancer and colon cancer cells. It is used as a potent antibacterial and antifungal agent being studied on the antibiotic-resistant bacterial and fungal strains recently, which can be further useful in developing herbal medicine against AMR. It is an excellent natural antioxidant due to the presence of polyphenolic compounds, and H. officinalis is used in various food industries as a source of natural antioxidants, which has minimum side effects as compared to artificial antioxidants. Furthermore, the pharmacological activity of these individual chemical constituents in H. officinalis extract still needs to be investigated for identifying the effectiveness of this plant in the natural treatment of various diseases. This review aims to collect various data regarding the traditional herbal plant hyssop (Hyssopus officinalis), including its photochemistry, chemical structures of the phyto-constituents and pharmacological profile, along with all the pharmacological models. This plant has significant importance in the health industry, so further studies are required on its effective usage against various emerging health problems, including COVID-19, cancer, diabetes, AMR.
Keywords: anti-anxiety